Persepsi Masyarakat tentang Tokoh Joker dalam Film Joker (Studi Kasus pada Penonton Film di Studio 21 Makassar Town Square) - Armadi Jaya Putra; Pramudita Budi Rahayu (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2020)
At the end of 2019 the people of Makassar were presented with a film with a background story and production from the United States with the title